2011
DOI: 10.1021/jm200750x
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytically Stable Cancer Targeting Peptides with High Affinity for Breast Cancer Cells

Abstract: Cancer cell targeting peptides have emerged as a highly efficient approach for selective delivery of chemotherapeutics and diagnostics to different cancer cells. However, the use of α-peptides in pharmaceutical applications is hindered by their enzymatic degradation and low bioavailability. Starting with a 10-mer α-peptide 18 that we developed previously, here we report three novel analogues of 18 that are proteolytically stable and display better (up to 3.5-fold) affinity profiles for breast cancer cells comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
87
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(91 citation statements)
references
References 52 publications
4
87
0
Order By: Relevance
“…Previous in vitro and in vivo studies for drug conjugates, such as DPV-maleimide, have shown that the use of TFA salts is not associated with any toxicity up to 1 mM concentrations. 28 These data reveal that both conjugates 1 and 2 are stable enough to allow sufficient time for cancer cell targeting.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…Previous in vitro and in vivo studies for drug conjugates, such as DPV-maleimide, have shown that the use of TFA salts is not associated with any toxicity up to 1 mM concentrations. 28 These data reveal that both conjugates 1 and 2 are stable enough to allow sufficient time for cancer cell targeting.…”
Section: Resultsmentioning
confidence: 85%
“…To facilitate side chain attachment to Dox, previously reported peptide 18-4 was synthesized with one substitution (r8k) and a C-terminal amide group. 28 This peptide is now referred to as 18-4a. Peptide 18-4a…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hilchie et al [19] designed a analog of NRC-03 by replacing all the original amino acids with the corresponding D-amino acids, named [D]-NRC-03, which exhibited higher anticancer activity than NRC-03 due to the stability against human serum or trypsin [21]. Except D-amino acid, other unnatural amino acids also have been used to modify the anticancer peptide to increase their stability or bioactivity [22][23][24]. Anticancer peptide of…”
Section: Introductionmentioning
confidence: 99%